Pacific finance sector brief Samoa. (Pacific finance sector briefs., 2019)
Samoa financial system comprises almost 30 licensed financial enterprises. These include two locally owned and two foreign owned commercial banks, six insurance companies, and four brokers. A provident fund, housing corporation, and a development bank are also established. The Central Bank of Samoa is the country monetary authority and primary regulator of financial institutions. While financial inclusion is relatively high here compared to other developing countries in the region, almost half of the adult population still lacks access to formal financial services. The government is currently undertaking a series of reforms to achieve a more inclusive financial system.